Decision Support for an Underground Gold Mining Operation - A Case Study using the Schedule Optimisation Tool - Fava, L.; Maybee, Bryan; Millar, D. (The Australasian Institute of Mining and Metallurgy, 2012)
In the context of a case study for an underground gold mine, the value generated by a schedule optimisation tool (SOT) is assessed. SOT is a software tool for underground mine planning that maximises the net present value (NPV) of a development and production schedule. A baseline study measures the NPV of a schedule generated by SOT from a sequence prepared by the site mine planners. Operational resource constraints and precedence constraints are adhered to by the schedule and NPV is evaluated with a financial model including revenues, costs and discount rate, as specified by the mine planner.The case study has several facets in addition to the baselining component. Scenarios were conducted that examined the degree of constraint on operational resources, the projected gold price and unit costs. Life-of-mine schedules subject to optimisation using SOT allowed for equitable comparisons. Haulage was identified as a dominant constraint for the mine. It was one of six operational resources that were used to constrain the optimisation of the mine schedule, with alternative levels for some of these constraints being identified so that their effects on the NPV could be studied. Alternative price projections for gold and different cost projections were identified and their effects on the optimised schedule examined. Price and cost scenarios that brought additional economic material into the schedule at various times in the mine life were considered in comparison to a scenario that assumed no additional economic material would become available.This case study illustrated that the use of a schedule optimisation tool to optimise mine schedules provides mine planners with an ability to perform a wide variety of analyses in a relatively short period of time. Such tools thereby support strategic decision-making that can add significant value to an orebody. The case study demonstrates that by fixing the set of development and production activities to be carried out before optimising the life-of-mine schedule, the mine planners can inadvertently set up a situation where the NPV would be progressively eroded in the last several years of the mine life. This clearly illustrates the need for schedule optimisation to be integrated with life-of-mine planning.